Obstetrical and perinatal complications in women with body weight deficiency - L. P. Shelestova; R. S. Allahverdiev; V. G. Syusyuka (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
The knowledge about the impact of body weight deficiency during pregnancy, childbirth and state of newborns is very important for obstetricians.